218 A Novel Role for the PMCA4-specific Inhibitor Aurintricarboxylic Acid as an Enhancer of VEGF-Induced Angiogenesis. (6th June 2015) - Kurusamy, Sathishkumar; Baggott, Rhiannon; Lopez-Maderuelo, Dolores; Little, Robert; Cadagan, David; Oceandy, Delvic; Cartwright, Elizabeth J; Rowther, Farjana B; Wang, Weiguang; Ludwig, Neyses; Miguel, Redondo Juan; Luis, Armesilla Angel
Abstract : Introduction: Angiogenesis, the formation of new blood vessels from pre-existing ones, is a tightly regulated process essential for proper embryonic development, organ growth and tissue repair. Changes in the expression of the pro-angiogenic factor Vascular Endothelial Growth Factor (VEGF) have been reported to play a major role in the progression of several human diseases, such as diabetic retinopathy, tumour growth and acute limb ischemia, by altering normal vascularisation. VEGF binding to specific tyrosine kinase receptors located on the surface of endothelial cells activates a variety of signal transduction pathways that switch on the expression of specific target genes. Among them, VEGF-mediated activation of the calcineurin/NFAT signalling pathway has been identified as a crucial regulator of both physiological and pathological angiogenesis. Our laboratory is interested in the characterisation of the molecular mechanisms that regulate the activity of the calcineurin/NFAT pathway during VEGF-induced angiogenesis. In this sense, we have recently identified a novel role for the Plasma Membrane Calcium ATPase 4 protein as a negative regulator of angiogenesis via interaction with calcineurin. We hypothesise that inhibition of PMCA4 will promote angiogenesis, and thus, PMCA4 inhibition might be used to induce therapeutic angiogenesis. Methods: To evaluate this hypothesis we have assayed VEGF-dependent proliferation, migration and tube formation in human primary endothelial cells treated with VEGF in the presence or absence of the PMCA4-specific inhibitor aurintricarboxylic acid (ATA). Results: We show here that inhibition of PMCA4 by ATA significantly increased the VEGF-induced activation of the calcineurin/NFAT pathway, and the subsequent expression of the NFAT-dependent, pro-angiogenic protein RCAN1.4 in HUVEC endothelial cells. Furthermore, VEGF-triggered endothelial cell migration and tube formation was also enhanced by treatment of the cells with ATA. Interestingly, ATA had no effect on endothelial cell tubular morphogenesis in response to Fibroblast Growth Factor (a pro-angiogenic protein that induces angiogenesis in a calcineurin-independent manner). Long term incubation of endothelial cells with ATA did not alter the viability of the cells, highlighting its potential use in clinic. Examination of the effect of ATA on the activity of other endothelial molecules regulated by PMCA4 has shown that ATA reduces the phosphorylation of endothelial nitric oxide synthase (eNOS) in the regulatory residue Thr495, suggesting that the ATA-mediated effect on angiogenesis might be consequence of upregulation of several PMCA4-regulated signalling pathways. Conclusion: Our results indicate that ATA might be used with therapeutic purposes to treat human diseases that occur with insufficient angiogenesis.